HUBUNGAN ANTARA PENGOBATAN TBC AKTIF DENGAN KEJADIAN DEPRESI DI PUSKESMASÂ LUMBANG PROBOLINGGO - Zainuri, Imam; Nur Hidayati, Anisa (JURNAL KEPERAWATAN SEHAT, 2014)
Tuberculosis (TB) requires long-term treatment to achieve a cure. Type of long-term treatment cause large numbers of patients in the treatment of non-compliance. The existence of Trustees Drink Drugs (PMO) of the patients family members are expected to recover in time and proper treatment. The purpose of this study was to analyze the correlation betweenthe active treatmenttuberculosis (TB) roleof patientsfamily with the incidence of depression. Design study using analytic correlational with cross sectional approach . The population in this study were all patients with active treatment of tuberculosis (TB) who lived with the family at the Lumbanghealth centers,Lumbangsub-district,Probolinggo are 32 respondents and 32 respondents sample was taken using a total sampling . Instrument research using questionnaires . Data collection was conducted in April 2014. Analyze data using cross-tabulations . The results showed most families are less active role in the treatment of tuberculosis as many as 20 respondents ( 62.5 % ) and the majority of people with mild depression Tuberculosis as many as 22 respondents (68.8 %) . The results of the analysis of data obtained from 32 respondents respondents most is getting a negative role and mild depression as many as 16 respondents ( 50 % ) while the least was the respondents who received a positive role and severely depressed respondents while also getting a negative role and not depressed as many as one respondent (3.1 %). families who have experienced family members Tuberculosis supervisor should be taking medication (PMO) for increasing the effectiveness of the role of the family is lacking in medical assistance due to family involvement in treatment can improve and monitor the treatment of patients with tuberculosis .Keywords : Role of Family, Tuberculosis, Depression.